Aerial pathways to resilience: the acceptance of drones in logistics transformation - Sofia Gomes; João M. Lopes; Tiago Trancoso (Future Business Journal)
Abstract Amidst the tumultuous backdrop of the COVID-19 pandemic and the ensuing lockdowns, traditional parcel delivery services faced substantial disruptions, grappling with challenges such as delays, heightened demand, and the inherent risk of contact transmission. In contrast, this paper explores the promising prospect of drone delivery services as a resilient and efficient alternative during crises, offering a contactless delivery solution to circumvent the limitations endured by traditional services in times of unprecedented upheaval. This study examines the determinants of consumer acceptance of drone delivery services, focusing on the roles of perceived usefulness, ease of use, and privacy concerns. We collected data from 1,108 Portuguese consumers through an online survey to assess how these factors influence consumer attitudes and intentions toward adopting drone delivery services. Our findings confirm that perceived usefulness is the most significant predictor of both positive attitudes toward and intentions to adopt drone delivery services, underscoring the importance of practical benefits in technology acceptance. Perceived ease of use also positively impacts consumer attitudes and intentions, highlighting the role of usability in facilitating adoption. Conversely, perceived privacy concerns, while negatively affecting attitudes and intentions, do so marginally, suggesting that privacy issues are secondary to the perceived benefits and usability of the service. The study further reveals that the mediation effect of consumer attitudes weakens the relationship between these antecedents and adoption intentions, particularly diminishing the negative impact of privacy concerns. This research not only provides valuable insights for businesses seeking to implement drone package delivery services but also offers a theoretical foundation for future studies in the burgeoning field of innovative logistics solutions. As industries evolve, it is imperative to unravel the complexities of consumer perceptions to foster successful integration and acceptance of cutting-edge technologies.